Technology Readiness as A Mediator Between Transformational Leadership and Digital Learning Effectiveness - Azhari, Widya Putri; Abidin, Munirul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Digital transformation in the education sector demands adaptive leadership and mature technology readiness to achieve the effectiveness of digital learning. This study aims to examine the relationship between transformational leadership and the effectiveness of digital learning, with technology readiness as a mediating variable. A quantitative approach was utilized through Structural Equation Modeling (SEM) based on SmartPLS 4. The research sample involved 52 teachers from various schools that have implemented digital learning using purposive sampling techniques. The instruments used included the Multifactor Leadership Questionnaire (MLQ), Technology Readiness Index (TRI), and indicators of digital learning effectiveness from Anderson (2008). The analysis results show that transformational leadership does not have a direct effect on the effectiveness of digital learning (p > 0.05), but has a significant effect on technology readiness (p < 0.001). Technology readiness significantly affects the effectiveness of digital learning (p < 0.001) and has been shown to mediate the relationship between transformational leadership and the effectiveness of digital learning. These findings emphasize the importance of technology readiness as a key to success in the implementation of effective digital learning. This research provides practical implications for educational institutions in designing sustainable digital transformation strategies that focus on human resource readiness.